Encounterological praxis of the Research Institute with African Initiated Churches: 1975–2025 - Mnyalaza T. Masuku (Verbum et Ecclesia)
The African Initiated Churches (AICs) suffered a sour relationship with churches and institutions of Western origin from where most originated. Western religious and political institutions adopted a polemic approach towards them. Their critique was primarily on their lack of theological training. This led to tension between them, levelling blames against each other making trust difficult. The Research Institute for Theology and Religion (RITR) was viewed as a Western entity that served colonial interests. Like the University of South Africa where it belonged over the 50 years of its existence, the RITR likewise, was judged as part of the drivers of the colonial project, infested with epistemic violence. It was placed in the same space as the mainline churches and their leadership that were polemic against them (AICs). How did the RITR explore and manage this tension with the AICs? In order to project a sustainable relationship between them, employing Kritzinger’s concept of ‘encounterology’ and drawing on existing literature through a qualitative review method, the author will critically examine the journey of their encounter to determine if it will be sustainable and become exemplary to others, more especially for ecumenism. The author will also propose sustainable strategic relationship goals between these two. The conclusion would be reached to determine if the RITR is doing or not doing enough to nurture and sustain this relationship.